The impact of using analytic rubrics for peer assessment and for self-assessment on students’ essay writing : - Phan, Quốc Toàn (Trường Đại học Cần Thơ, 2019)
The current study was conducted to investigate into the impact of using analytic rubrics for peer assessment and for self-assessment on students’ essay writing performance. It was carried out with the participation of 38 students who were students from high schools and universities. They registered for the B1-level learning course at an English language center in Can Tho city in Vietnam.